The Influence of Learning Models Questions Students Have Regarding Students' History Social Studies Learning Outcomes - Vianata, Haning (Indonesian Journal of History Education, 2016)
IPS needs an innovative learning model to improve learning outcomes. This study intends to examine the influence of innovative learning models Have Student Question (QSH) on the learning outcomes of Sejarah students. The study was conducted in class VIII SMPN 1 Kendal. The conclusion of this study is: In the experimental class, the average score was 78, with the highest score of 95 and the lowest score of 65. In the control class, the average score was 69. The highest score was 85, and the lowest score was 60. The difference is insignificant because the question tests have lower difficulty levels. In the post-test, the average of the experimental class was 77.97, and the average grade in the control class was 69.35. There is a correlation between students' good results and the Student’s Question Have learning model.